Role of Visual Arts in Student's Academic Performance - Charu Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Arts have long been considered part of the human affective experience and needed by our young people as a medium for safe expression, communication, exploration, imagination, cultural and historical understanding. Thus, the challenge for Visual Arts integration should not focus only on a particular art discipline alone like Humanities (Art Appreciation) somewhat it should extend across the curriculum. The major problem of this study was to assess the impact of visual art on the performance of the students from the Institute of engineering & management, Dehradun. The study made use of experimental research design. Results of the study revealed that significant difference exists in the post-test performances of the experimental and control groups, in other words, the group who utilized the visual arts in studying art appreciation recorded significantly helps performance than those who used the traditional lecture-discussion method. Moreover, further analysis of data suggested that using visual arts in different learning areas encourages students to participate and this will develop their confidence and advantage in the learning process. Some pedagogical implications were drawn based on the findings of the study.
Keywords: Drawing and Painting; Visual Art; Academic Performance